2011
DOI: 10.1590/s0104-530x2011000300012
|View full text |Cite
|
Sign up to set email alerts
|

Análise das estratégias de produção de seis montadoras de motores para automóveis

Abstract: Abstract:The operations strategies adopted by six engine assemblers between 2005 and 2006 Resumo: São identificadas e analisadas neste artigo as Estratégias de Produção (EP) adotadas, durante o período 2005-2006, por 6 empresas montadoras de motores para automóveis instaladas no Brasil. Três delas instalaram-se há várias décadas no País e são aqui denominadas "estabelecidas"; as outras três, apenas há alguns anos, são denominadas "entrantes". Para o levantamento de informações sobre as EPs adotadas, entrevis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(2 reference statements)
1
4
0
1
Order By: Relevance
“…Case studies were carried out in two automotive engine manufacturers, which were intentionally selected because (1) they belong to different strategy groups (one is a mature company set up in brazil since the 50s/60s, while the other is a newcomer set up in the country in the late 90s); (2) previous investigation carried out by our research group (Alves Filho et al, 2006) indicated that they keep important similarities with other companies from their strategic groups, but also keep important differences between them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies were carried out in two automotive engine manufacturers, which were intentionally selected because (1) they belong to different strategy groups (one is a mature company set up in brazil since the 50s/60s, while the other is a newcomer set up in the country in the late 90s); (2) previous investigation carried out by our research group (Alves Filho et al, 2006) indicated that they keep important similarities with other companies from their strategic groups, but also keep important differences between them.…”
Section: Methodsmentioning
confidence: 99%
“…First of all, it is worth to mention that this paper do not intend to make generalizations about mature companies and newcomers in brazilian automotive industry. However, its important to mention several studies by Cerra (2007), Alves Filho et al (2006, Consoni (2004), which argue that, regarding operations and technological strategies in this industry, 1) mature engine manufacturers keep important similarities among them, 2) newcomers are even more similar inside their group, and 3) mature companies and newcomers are different when compared with one another. this fact suggests that the companies here studied may bring meaningful information about the trajectories followed by companies belonging to brazilian automotive industry.…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%
“…In the case of the automotive industry, it is noted that it is currently seeking to maintain networks with fewer suppliers, longer-term relationships, and greater integration with suppliers, so that all participants actively contribute to increase the automakers' competitiveness [22]. Lockstrom, Schadel, Moser and Harrison [23] assess the concept of the supply chain for the automotive industry, considering it unlikely that a single company would be able to produce all the components of a car.…”
Section: The Automotive Supply Chainmentioning
confidence: 99%
“…Figure 1 adapts the model of Lambert and Cooper [1] to the case of the automotive supply chain -the focus of the present study. Alves Filho, Nogueira and Bento [22], in a survey of car engine manufacturers in Brazil, find that the most relevant competitive priorities are flexibility, cost, quality, and reliability of delivery. Their research also presents other results, including suppliers being located closer to one another and the adoption of lean manufacturing practices in order to support the identified competitive priorities.…”
Section: The Automotive Supply Chainmentioning
confidence: 99%
“…Parece, portanto, coerente a valorização de ferramentas de Gestão de Operações que os instrumentalizem para o bom desempenho dessas atribuições. Este resultado corrobora os achados de Ford et al (2003), para quem os executivos valorizam o conhecimento como uma fonte de vantagem competitiva, bem como os de Alves et al (2011), que identificaram a implementação de um sistema de gestão baseado no lean manufacturing como o principal movimento estratégico de produção nas empresas por eles estudadas.…”
Section: Identificação Das Dimensões Dos Temas De Gestão De Operaçõesunclassified